2012
DOI: 10.2166/wst.2012.293
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the sensitivities of fish, Microtox and Daphnia-magna bioassays to amoxycillin in anaerobic/aerobic sequential reactor systems

Abstract: In this study the anaerobic treatability of amoxycillin (AMX) was investigated in a laboratory-scale anaerobic multi-chamber bed reactor (AMCBR)/aerobic continuously stirred tank reactor (CSTR) system. The chemical oxygen demand (COD) and AMX removal efficiencies were around 94% in the AMCBR reactor at hydraulic retention times (HRTs) between 2.25 and 5.5 days. Decreasing the HRT appeared not to have a significant effect on the performance of the AMCBR up to a HRT of 1.13 days. The maximum methane production r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…fischeri was also the most sensitive species in the study by Çelebi and Sponza (2012), who observed an increase in the toxicity when the HRT was reduced to 0.9 days, which resulted in a reduction in the biogas production and an increase in the volatile fatty acids concentration that could enhance the effluent toxicity.…”
Section: Anaerobic Digester (Biostat)mentioning
confidence: 90%
See 4 more Smart Citations
“…fischeri was also the most sensitive species in the study by Çelebi and Sponza (2012), who observed an increase in the toxicity when the HRT was reduced to 0.9 days, which resulted in a reduction in the biogas production and an increase in the volatile fatty acids concentration that could enhance the effluent toxicity.…”
Section: Anaerobic Digester (Biostat)mentioning
confidence: 90%
“…Seed Germination test, Aliivibrio fischeri and Raphidocelis subcapitata were chosen due its advantages in terms of simplicity, cost effectively, reproducibility and low time to obtain the results. A. fischeri is a very sensitivity specie that has been widely used for wastewater monitoring and can be applied for a large number of compounds, including amoxicillin (Çelebi and Sponza, 2012;Di Nica et al, 2017).…”
Section: Ecotoxicological Testsmentioning
confidence: 99%
See 3 more Smart Citations